ORNAMEN PURA PENATARAN BUJANGGA SANGGING PRABANGKARA BANJAR KEBON KECAMATAN BLAHBATUH GIANYAR PERSPEKTIF PENDIDIKAN SENI RUPA KEAGAMAAN HINDU - I Nyoman Putra Adnyana; I Kadek Sumadiyasa (UNHI PRESS, 2019)
Ornaments of Penataran Bujangga Sangging Prabangkara Temple Kebon Village Blahbatuh Gianyar, is one of the forms of Hindu religious fine art education which is very unique in its visual working process hereditary done incompletely as a means of religious belief, in its development become a phenomenon in its field. So it is interested to be examined under the title